Improving health care quality for racial/ethnic minorities: a systematic review of the best evidence regarding provider and organization interventions - Smarth Carole; Palacio Ana; Gozu Aysegul; Robinson Karen; Price Eboni G; Gary Tiffany L; Beach Mary; Jenckes Mollie; Feuerstein Carolyn; Bass Eric B; Powe Neil R; Cooper Lisa A (BMC, 2006)
Abstract Background Despite awareness of inequities in health care quality, little is known about strategies that could improve the quality of healthcare for ethnic minority populations. We conducted a systematic literature review and analysis to synthesize the findings of controlled studies evaluating interventions targeted at health care providers to improve health care quality or reduce disparities in care for racial/ethnic minorities. Methods We performed electronic and hand searches from 1980 through June 2003 to identify randomized controlled trials or concurrent controlled trials. Reviewers abstracted data from studies to determine study characteristics, results, and quality. We graded the strength of the evidence as excellent, good, fair or poor using predetermined criteria. The main outcome measures were evidence of effectiveness and cost of strategies to improve health care quality or reduce disparities in care for racial/ethnic minorities. Results Twenty-seven studies met criteria for review. Almost all (n = 26) took place in the primary care setting, and most (n = 19) focused on improving provision of preventive services. Only two studies were designed specifically to meet the needs of racial/ethnic minority patients. All 10 studies that used a provider reminder system for provision of standardized services (mostly preventive) reported favorable outcomes. The following quality improvement strategies demonstrated favorable results but were used in a small number of studies: bypassing the physician to offer preventive services directly to patients (2 of 2 studies favorable), provider education alone (2 of 2 studies favorable), use of a structured questionnaire to assess adolescent health behaviors (1 of 1 study favorable), and use of remote simultaneous translation (1 of 1 study favorable). Interventions employing more than one main strategy were used in 9 studies with inconsistent results. There were limited data on the costs of these strategies, as only one study reported cost data. Conclusion There are several promising strategies that may improve health care quality for racial/ethnic minorities, but a lack of studies specifically targeting disease areas and processes of care for which disparities have been previously documented. Further research and funding is needed to evaluate strategies designed to reduce disparities in health care quality for racial/ethnic minorities.